Konseling Kelompok Cognitive Behaviour Untuk Meningkatkan Konsep Diri Positif Siswa SMA - Putra, Rico Wardana; Christiana, Elisabeth; Habsy , Bakhrudin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
The benefits of CBT-based counseling services have been widely proven, one of which is through the implementation of this research that evaluated the effectiveness of CBT services in group counseling programs at the high school level to optimize their self-concept. By utilizing a true experimental study setting involving a number of students to carry out the intervention. Data processing went through multi-stage stages starting from paired sample T-test testing with a significance of 0.05. The research also conducted pretest and posttest stages to see differences in experimental results on the t-table, namely degrees of freedom (dk) N-1, and a significance of α = 0.05. The output of the data processing found a t-table value of 1.782, so Ha is